2023
DOI: 10.1038/s41598-023-33927-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and hepatic histopathological findings of fascioliasis in sheep slaughtered in Jeddah, Saudi Arabia

Abstract: Hepatic fascioliasis is an important parasitic disease responsible for morbidity and mortality in many domestic ruminants, especially sheep, goats, and cattle, due to Fasciola (F.) hepatica and F. gigantica. This study aimed to determine the prevalence of fascioliasis in sheep slaughtered in Jeddah, Saudi Arabia, and to describe the morphological and histopathological changes in the liver. A total of 109,253 sheep slaughtered between July 2017 and July 2018 were screened to assess the prevalence of fascioliasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…Typical lesions of chronic fasciolosis, such as bile duct hyperplasia, portal fibrosis, lymphocyte and plasma cell inflammatory infiltrate, chronic tracks, and globule leukocyte infiltration in bile ducts were found mainly at 100 dpi in the PI and RI groups as well as in early stages of infection in the RI groups, confirming results of previous studies in which these lesions were reported in chronic fasciolosis [ 21 , 25 , 26 , 27 , 29 , 39 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Typical lesions of chronic fasciolosis, such as bile duct hyperplasia, portal fibrosis, lymphocyte and plasma cell inflammatory infiltrate, chronic tracks, and globule leukocyte infiltration in bile ducts were found mainly at 100 dpi in the PI and RI groups as well as in early stages of infection in the RI groups, confirming results of previous studies in which these lesions were reported in chronic fasciolosis [ 21 , 25 , 26 , 27 , 29 , 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the RI groups, the inflammatory infiltration of eosinophils was more severe than in the PI groups, probably due to the higher number of metacercariae received and more severe hepatic necrotic tracks. This severe eosinophil infiltration found in the RI groups may play a role in the predominance of a Th2 response characterized by the production of IL-4 and IL-5 [37,38] and it agrees with the severe infiltration of eosinophils in naturally F.-hepatica-infected sheep [39] Typical lesions of chronic fasciolosis, such as bile duct hyperplasia, portal fibrosis, lymphocyte and plasma cell inflammatory infiltrate, chronic tracks, and globule leukocyte infiltration in bile ducts were found mainly at 100 dpi in the PI and RI groups as well as in early stages of infection in the RI groups, confirming results of previous studies in which these lesions were reported in chronic fasciolosis [21,[25][26][27]29,39].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations